Strategi Komunikasi Interpersonal Guru Dalam Mengatasi Dampak Smartphone Pada Perkembangan Komunikasi Siswa Kelas 6 Sdn 04 Batipuah - Wahyuni, Rahmi Sri; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Technological advancements, including the development of smartphones, have both positive and negative impacts on human life. Excessive use of smartphones among children, especially elementary school students, can hinder their communication development. This study aims to examine teachers' interpersonal communication strategies in addressing the negative impacts of smartphone use on the communication development of 6th-grade students at SDN 04 Batipuah Baruah, Tanah Datar Regency, West Sumatra Province. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The results show that effective interpersonal communication between teachers and students can mitigate the negative impacts of smartphone use and support students' communication development. The strategies implemented include individual approaches, monitoring smartphone usage, and wise integration of technology into the learning process. Teachers use various techniques to interact directly with students, build closer relationships, and understand their needs and difficulties. Additionally, teachers provide guidance and direction on the appropriate and healthy use of smartphones. Technology integration in learning is carried out carefully so that students can utilize smartphones as learning tools without neglecting the aspects of interpersonal communication. This study provides significant contributions to the field of education by offering practical solutions to overcome the negative impacts of technology on children.